Characterization of hexavalent chromium interaction with Sargassum by X-ray absorption fine structure spectroscopy, X-ray photoelectron spectroscopy, and quantum chemistry calculation - Zheng, Y.-M. (2014)
10.1016/j.jcis.2010.12.070